Chlojaponilactone B Attenuates THP-1 Macrophage Pyroptosis by Inhibiting the TLR/MyD88/NF-κB Pathway - Qiyin Wen; Bingjinfeng Zhan; Lu Jin; Zijing Peng; Ju Liu; Longping Zhu; Depo Yang; Xinjun Xu; Lixia Zhang; Ge Li; Zhimin Zhao (MDPI AG, 2024)
Pyroptosis, an innate immune response, plays a crucial role in the pathological process of inflammatory diseases. Although pyroptosis blockade is considered a potential therapeutic strategy, no ideal candidate drug has been identified. The natural product Chojaponilactone B (CJB) has demonstrated anti-inflammatory effects, but its role in macrophage pyroptosis has not been studied. This study aimed to investigate the effect and mechanism of CJB in inhibiting macrophage pyroptosis. Using an LPS/ATP-induced THP-1 macrophage pyroptosis model, we found that CJB significantly inhibited pyroptosis and reduced the levels of NLRP3, caspase 1, N-GSDMD, and inflammatory cytokines IL-1β and IL-18. RNA sequencing analysis revealed that CJB interfered with LPS/ATP-induced THP-1 macrophage gene expression, suggesting involvement in anti-inflammatory and anti-pyroptotic signaling pathways. Additionally, CJB suppressed LPS/ATP-induced elevations in TLRs, MyD88, pro-IL-1β, and NF-κB and blocked NF-κB p65 nuclear translocation. In summary, CJB inhibits NLRP3 activation and macrophage pyroptosis through the TLR/MyD88/NF-κB pathway, providing important evidence for its development as a potential drug for treating pyroptosis-related inflammatory diseases.